Physical demands and muscle-induced damage in women's rugby union World Cup matches - Imbert, S.; Piscione, J.; Joncheray, H.; Daussin, F. N. (The Journal of Strength and Conditioning Research, 2025)
Increasing professionalization of women's rugby union is leading to a continuous increase in the level of practice and physical performance. The study aimed to determine the physical demands of international matches during the World Cup, match-induced muscle damage, and the relationship between blood measurement and Global Positioning System (GPS) parameters and/or subjective questionnaires. A total of 26 women's rugby union players were monitored through GPS during 6 matches of the 2022 Rugby World Cup. Eleven GPS parameters were analyzed: playing time, total distance, walking percentage, maximal aerobic speed, activity percentage, number of accelerations and decelerations, high- and very high-intensity distance, sprint distance, and maximum speed. Maximal distance was determined using rolling windows of 30 seconds, 1 minute, and 2 minutes. Well-being questionnaires and blood creatine kinase (CK) were monitored 36 hours after a match. Outside backs run faster and cover greater distances at > 24 km·h-1 than other positions, and half backs cover the greatest total distance (p < 0,05) and accelerate more (p < 0,02) than other positions. Worst-case scenario (WCS) analysis also revealed that half backs run a greater distance than other positions (p < 0.05). Blood CK activity increased 4-fold 36 hours after a match. Global Positioning System data and subjective surveys do not reflect muscle damage but, on a larger scale, they are tools to study fatigue in international rugby players. The physical demands during a match are different depending on the position played, and WCS data are useful for preparing the players. Muscle damage could not be assessed with the noninvasive tools used here.